Understanding black landowner's engagement in forestry in Georgia, United States: a closer look. Issue 4 (2nd October 2021) - Schelhas, John; Hitchner, Sarah; Dwivedi, Puneet; Thomas, Marc
ABSTRACT: Black rural land ownership and agriculture in the U.S. South have declined markedly over the past century. The challenges of farming and the rise of off-farm employment mean that forestry is often the most appropriate productive land use choice, yet engagement in forest management is often limited in Black landowners. The literature has identified the primary obstacles for forestry as land ownership issues such as heirs' property, a disconnect between Black landowners and forestry professionals, and poor access to the conservation assistance programs supporting family forestry. Yet our understanding of these factors is incomplete. This paper provides an in-depth exploration of the factors influencing forestry engagement by Black landowners in the U.S. South based on in-person, semi-structured interviews and analysis of the resulting quantitative and qualitative data. The results suggest that past discrimination has often led to smaller landholdings and insecure land tenure, which limit forestry engagement. In addition, we find that forestry engagement is further hindered by family disagreement, as well as research and outreach initiatives that fail to acknowledge traditional forest use and management practices and narrowly focus on technical forestry while ignoring social contexts.